Practical English Communication: Role plays training for SMKN 1 Majene students - Marliana, Rina; Ali H, Ali H; Warqiah R, Warqiah R; Syamsul, Cici Pracilia (Room of Civil Society Development, 2025)
Vocational high school students in Indonesia are expected to develop English proficiency aligned with workplace demands, yet grammar-focused instruction often limits their communicative competence. Role-play, as an interactive and learner-centered approach, offers potential to enhance speaking skills in vocational contexts. Through a service-learning framework, this community engagement project involved lecturers, students, and teachers in collaboratively implementing role-play activities based on authentic scenarios in hospitality and fashion design. Students engaged in simulated real-life interactions that promoted active participation, peer collaboration, and pragmatic language use. Data from observations, questionnaires, and student reflections indicate that role-play significantly improved engagement, motivation, and speaking confidence. Quantitative results show 54.5% of students found the method engaging, 75.8% viewed the materials as clear, and 78.1% recognized the PkM team’s effective delivery. Qualitative feedback highlighted gains in vocabulary, practical communication skills, and readiness to apply English beyond the classroom. Embedding role-play into vocational English instruction thus addresses gaps in speaking practice and supports the development of workplace-relevant communication. This study contributes to ongoing discussions of role-play as an effective pedagogical strategy in ESL/EFL classrooms, particularly within vocational education where practical language use is essential.